Transstadial Transmission and Long-term Association of Crimean-Congo Hemorrhagic Fever Virus in Ticks Shapes Genome Plasticity - GARGILI KELEŞ, AYŞEN (NATURE PUBLISHING GROUP, 2016)
The trade-off hypothesis, the current paradigm of arbovirus evolution, proposes that cycling between vertebrate and invertebrate hosts presents significant constraints on genetic change of arboviruses. Studying these constraints in mosquito-borne viruses has led to a new understanding of epizootics. The trade-off hypothesis is assumed to be applicable to tick-borne viruses too, although studies are lacking. Tick-borne Crimean-Congo hemorrhagic fever virus (CCHFV), a member of the family Bunyaviridae, is a major cause of severe human disease worldwide and shows an extraordinary amount of genetic diversity compared to other arboviruses, which has been linked to increased virulence and emergence in new environments. Using a transmission model for CCHFV, utilizing the main vector tick species and mice plus next generation sequencing, we detected a substantial number of consensus-level mutations in CCHFV recovered from ticks after only a single transstadial transmission, whereas none were detected in CCHFV obtained from the mammalian host. Furthermore, greater viral intra-host diversity was detected in the tick compared to the vertebrate host. Long-term association of CCHFV with its tick host for 1 year demonstrated mutations in the viral genome become fixed over time. These findings suggest that the trade-off hypothesis may not be accurate for all arboviruses.
Keywords: ADULT HYALOMMA-TRUNCATUM; RNA VIRUS; ENCEPHALITIS-VIRUS; FITNESS; DIVERSITY; REPLICATION; EPIDEMIOLOGY; POPULATION; ACARI; PATHOGENESIS